Fabrication of an enriched graphene surface protection of carbon fiber/epoxy composites for lightning strike via a percolating-assisted resin film infusion method. (12th April 2018) - Wang, Ben; Duan, Yugang; Xin, Zhibo; Yao, Xueling; Abliz, Dilmurat; Ziegmann, Gerhard
Abstract: A low-conductivity feature of carbon fiber-reinforced polymers (CFRP) needs to be engineered with lightning strike protection to decrease the vulnerability of the material to lightning strike damage. This paper reports a percolating-assisted resin film infusion method that achieves a conductive lightning strike protection via the accumulation of reduced graphene oxide (RGO) on the composite surface. In this method, the fibrous preform was sealed by the filter paper and the sealant tape to form a confined region that avoids the expansion of RGO from the fibrous preform while also limiting the RGO flow along the thickness direction, and thus RGO accumulates on the CFRP surface through filtration mechanisms. The enriched RGO on CFRP allowed high conductivity values (440 S/cm vs. 16 S/cm of CFRP) on the surface while also improving the thermal resistance of CFRP. As a result, RGO protection dramatically improved the lightning damage resistance as compared to CFRP. The residual strength, characterized via 3-point flexural testing after a simulated lightning test, only decreased by 23% as compared to its initial value, whereas a drastic reduction (66%) was observed for pristine CFRP.